Exploring Students’ Engagement in Blended Learning - Siti Alawiyah Aini; Dyah Setyowati Ciptaningrum (Britain International for Academic Research (BIAR) Publisher, 2024)
The COVID-19 pandemic brought significant changes to education, prompting a shift to blended learning post-2022. A study conducted with 250 English Education master's students at Universitas Negeri Yogyakarta explored student engagement in this new learning model. Using an adapted engagement scale and assessing barriers and efforts, researchers found moderate engagement levels with low barriers. Students actively worked to maintain their engagement, regardless of gender or age, though differences in engagement levels did surface between males and females, and across age groups. Interestingly, efforts and barriers didn't significantly vary by gender or age. The study concluded that both barriers to engagement and students' efforts strongly influenced their overall engagement in blended learning. These findings highlight the adaptability and commitment of students in navigating blended learning environments, underscoring its effectiveness as a teaching approach post-pandemic.